High spatial and temporal resolution cerebrovascular reactivity for humans and large mammals: A technological description of integrated fNIRS and niABP mapping system - Sainbhi, Amanjyot Singh; Froese, Logan; Gomez, Alwyn; Marquez, Izzy; Amenta, Fiorella; Batson, Carleen; Stein, Kevin Y.; Zeiler, Frederick A. (Frontiers in Physiology, 2023)
The process of cerebral vessels maintaining cerebral blood flow (CBF) fairly constant over a wide range of arterial blood pressure is referred to as cerebral autoregulation (CA). Cerebrovascular reactivity is the mechanism behind this process, which maintains CBF through constriction and dilation of cerebral vessels. The Lassen autoregulatory curve visually depicts CA by plotting CBF against cerebral perfusion pressure or mean arterial pressure. Traditionally CA has been assessed statistically, limited by large, immobile, and costly neuroimaging platforms. However, with recent technology advancement, dynamic autoregulation assessment is able to provide more detailed information on the evolution of CA over long periods of time with continuous assessment. Yet, to date, such continuous assessments have been hampered by low temporal and spatial resolution systems, that are typically reliant on invasive point estimations of pulsatile CBF or cerebral blood volume using commercially available technology. Using a combination of multi-channel functional near-infrared spectroscopy and non-invasive arterial blood pressure devices, we were able to create a system that visualizes CA metrics by converting them to heat maps drawn on a template of human brain. The generation of the heat maps are entirely non-invasive, with high temporal and spatial resolution. Within, we outlined the rationale, background, and technical specifications of this novel neuroimaging system.